If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.92y + 2 = y + -0.4 Reorder the terms: 2 + 0.92y = y + -0.4 Reorder the terms: 2 + 0.92y = -0.4 + y Solving 2 + 0.92y = -0.4 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2 + 0.92y + -1y = -0.4 + y + -1y Combine like terms: 0.92y + -1y = -0.08y 2 + -0.08y = -0.4 + y + -1y Combine like terms: y + -1y = 0 2 + -0.08y = -0.4 + 0 2 + -0.08y = -0.4 Add '-2' to each side of the equation. 2 + -2 + -0.08y = -0.4 + -2 Combine like terms: 2 + -2 = 0 0 + -0.08y = -0.4 + -2 -0.08y = -0.4 + -2 Combine like terms: -0.4 + -2 = -2.4 -0.08y = -2.4 Divide each side by '-0.08'. y = 30 Simplifying y = 30
| 16=7+3 | | 8x+8=4x+3z | | (4x^2)=8x-5 | | 4c(c-d)=60 | | 25-6m+4=41 | | (y+6)-(5y+1)= | | 3T=17 | | -2a^2+10a-12=0 | | 3(t-5)+5t=4(2t+5)-12 | | 15+2(x-1)=3(2x+1)-18 | | -7(3x-10)-6(4x+8)= | | 2x+16=3x-15 | | 3n-5=-8(4+5n) | | 6x^3-3x^2-18x=0 | | 2(4x-3)-6=4+2x | | x^2-6x-39=0 | | 3x+32=12x-49 | | -2(3x+9)+10(9x+2)= | | 7x-3=ax+5b | | 2(3x-1)=3(2x-3)+3 | | 75+2t=100-2T | | 120-5x=31x+20 | | -14-7x=8+16 | | 7-8x=106-29x | | 2x+2y=8 | | 5z+16=51 | | 220-5x=40x+20 | | 2x+3x=5x+1 | | 5x+2y+8= | | 12b-4=16 | | 6+8x=12+6 | | 9-9x=47-16x |